Comparative evaluation of phytochemical screening, in vitro antioxidant & α-Glucosidase inhibitory properties of Ceiba pentandra & Basella rubra leaf extracts: Identification of active principles by Q-TOFLCMS, ADMET prediction & molecular docking approach - Ananda, Zahradifa Kaniabila; Begum, Taslima; Ahda, Mustofa; Rofiee, Mohd Salleh; Ali Shah, Syed Adnan; Salleh, Mohd Zaki; Almutairi, Bader O.; Azmi, Syed Najmul Hejaz; Sah, Pankaj; Wardani, Agustin Krisna; Khatib, Alfi; Abbas, Syed Atif; et al. (Scientific Scholar on behalf of King Saud University, 2025)
Ceiba pentandra and Basella rubra leaves are traditionally used in Indonesia to treat ailments like diabetes. This study aimed to validate their use by assessing their antioxidant and α-glucosidase inhibitory properties. Initially, maceration of the leaves of both plants yielded dichloromethane, methanol (MeOH), and aqueous extracts. These were phytochemically profiled, and the most active extracts underwent quadrupole time of flight- liquid chromatography mass spectrometry (Q-TOF LCMS) analysis to identify potentially active principles, followed by molecular docking to ascertain their mechanism of action. The results revealed that the aqueous and methanolic extracts of C. pentandra exhibited potent antioxidant activities, with IC50 values of 17.66 ± 0.7 and 53.58 ± 0.25 µg/mg ascorbic acid equivalent for ferric reducing antioxidant power, respectively. In comparison, the aqueous and methanolic extracts of B. rubra showed lower antioxidant potential, with values of 8.73 ± 0.1 and 10.17 ± 0.08 µg/mg AAE, respectively. Additionally, the DPPH assay displayed that the aqueous and methanolic extracts of C. pentandra had IC50 values of 157.32 ± 3.44 and 27.71 ± 1.54 µg/mL, respectively. In contrast, the aqueous and methanolic extracts of B. rubra had higher IC50 values of 661.78 ± 1.8 and 253.76 ± 2.4 µg/mL, respectively. Owing to their significantly higher antioxidant activity, the aqueous and methanolic extracts of C. pentandra leaves also displayed better α-glucosidase inhibitory effects compared to B. rubra, with IC50 values of 109.54 ± 1.72 and 10.78 ± 0.48 µg/mL, respectively. Q-TOF LCMS analysis of C. pentandra’s methanolic extract identified significant bioactive compounds, including m-coumaric acid (1), cis-β-d-Glucosyl-2-hydroxycinnamate (2), luteolin 7-rhamnosyl (1->6)galactoside (3), avenanthramide 2s (4), robinetin 3-rutinoside (5), melanoxetin (6), scutellarein 7-glucoside (7), torosaflavone B 3’-O-β-d-glucopyranoside (8), and 2’’-O-α-l-rhamnosyl-6-C-fucosyl-3’-methoxyluteoiin (9). Molecular docking analysis showed that compounds 7, 8, and 3 were the most active with protein 3A4A, having affinity energies of -9.7, -10.0, and -10.3 kcal/mol, respectively. These phenolic compounds could be safe α-glucosidase inhibitors for diabetes treatment